2018
DOI: 10.1177/0095798418783561
|View full text |Cite
|
Sign up to set email alerts
|

African American Gender Roles: A Content Analysis of Empirical Research From 1981 to 2017

Abstract: The purpose of this study was to explore how gender roles research has been conducted among African Americans in the psychological literature. Accordingly, we completed a content analysis of empirical studies on this topic. We utilized the Table of Contents of several psychology journals, psychological databases, and search engines to identify relevant literature. Articles included for review met the following criteria: (a) published between 1981 and 2017, (b) empirically based, (c) psychologically focused on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 94 publications
(273 reference statements)
0
9
0
Order By: Relevance
“…Previous research has indicated that instead of formal mental health service providers, African Americans tend to rely on more informal sources of support in grief, such as church and church family (Cai & Robst, 2016;Chatters, Taylor, Woodward, & Nicklett, 2015;K. Hays & Aranda, 2016;Holt et al, 2017;Jones et al, 2018). Ninety-two percent of African Americans indicate that religion and church attendance is very important to them and that they are hesitant to seek mental health providers for their mental health issues; for example, grief, because therapy would take away from their religious beliefs (Chatters, Taylor, Woodard, et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous research has indicated that instead of formal mental health service providers, African Americans tend to rely on more informal sources of support in grief, such as church and church family (Cai & Robst, 2016;Chatters, Taylor, Woodward, & Nicklett, 2015;K. Hays & Aranda, 2016;Holt et al, 2017;Jones et al, 2018). Ninety-two percent of African Americans indicate that religion and church attendance is very important to them and that they are hesitant to seek mental health providers for their mental health issues; for example, grief, because therapy would take away from their religious beliefs (Chatters, Taylor, Woodard, et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers have also found that aggregate adapting and thinking about others and covering of feelings were normal (Chandler, 2020;K. Hays & Lincoln, 2017;Jones et al, 2018;Morrison & Hopkins, 2019;Park et al, 2018;Robinson et al, 2018;Sargent et al, 2019).…”
Section: The Use Of Religion and Spirituality Is A Means Of Coping And Resilience By African Americansmentioning
confidence: 93%
See 3 more Smart Citations